Использование сервисов Веб 2.0 в преподавании и изучении иностранных языков - Беловенцева, М.В.; Трунченкова, Н.Н. (Культура народов Причерноморья, 2013)
Целью статьи является анализ и обобщение исследований зарубежных и отечественных методистов, изучающих роль сервисов Веб 2.0 в образовании, а также разработка списка веб-ресурсов для работы над всеми видами иноязычной речевой деятельности. Ключевые слова: Веб 2.0, системы хранения закладок, Wordle, блог, обучение иностранным языкам. Метою статті є аналіз і узагальнення досліджень зарубіжних і вітчизняних методистів, що вивчають роль сервісів Веб 2.0 в освіті, а також розробка списку веб-ресурсів для роботи над всіма видами мовної діяльності. Ключові слова: Веб 2.0, системи зберігання закладок, Wordle, блог, вивчення іноземних мов. New Web 2.0 technologies provide students at all levels with a different way of communicating and cooperating, simple creating, exchanging and commenting on their contents, learning in a more interesting way and the independent publishing of projects and other papers. The aim of the article is to analyse and generalize researches of foreign and Ukrainian methodologists into the role of Web 2.0 services in education. An overview of the basic characteristics of Web 2.0 is presented. Such features of Web 2.0 as sociability, availability, creativity and interactivity make it a powerful device for teaching and learning foreign languages. Web 2.0 services are classified according to the language skills they can be used to develop, and a list of web resources helpful in teaching reading, writing, listening and speaking is compiled. Possibilities of incorporating such resources as blogs, bookmarking services, word cloud generators into educational process are analysed. Blogs are considered to be one of the key social tools of Web 2.0 as all other technologies can be used inside a blog. They possess high methodological potential in the sphere of the foreign language teaching. The research enables the authors to draw the conclusion that the integration of Web 2.0 services can assist in solving such didactic tasks as reinforcement of students’ independence, responsibility and creativity, raising motivation and development of informational, sociocultural and professional competences. Key words: Web 2.0, bookmarking services, Wordle, blog, teaching foreign languages.